(3GdMGUd ef GdeMUhds - (3eMeO Hf MSf GdCQehis; (3GdaNQ GdQGRj , GdaNQ GdQGRj,J (B606 (3g` s
(3ChdgG (B:s
(3hgh EeG HOhf GdHjGf hgh eQJH Ydi ebOeI hKdGKI CbSGe s
(3BNQgG (B:s
(3gPG GdeYfi jJMbb ai GdaQY ajdRe GdJYOi s
(3HChdg agQSs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1615s
Keywords: (3CUhd Gdabgs